Tendencies of the Zionist Movement in Lithuanian Republic (1918 - 1940) - Bendikaitė, Eglė (Sociologija. Mintis ir veiksmas, 2001)
The Zionism movement, as elswhere in the world, was not a united movement in Lithuania. It was divided between competing political factions, more or less influential at different periods, debating means and ends, and its relation with the Lithuanian state. The main goal of the Zionists was to prepare Jews for emigration to Palestine, and to foster the Hebrew language and national culture. The General Zionists and Zionist Socialists had the biggest influence on Lithuanian Jewish communities in the period of 1918 - 1940. The primary Zionist support for Jewish cultural work and national upbringing was through Jewish schools and the press. The prosperity of the Zionist press in the interwar period was weighty proof, that Lithuanian Jewry supported Zionist ideas. The greatest achievement of the Lithuanian Jewish national minority, which was kept up in the whole interwar period, was the independent educational system. The dominant part of the Jewish educational system was the Tarbut school network. There were a whole complex of the historical and political factors, which comprised the environment in which the Zionist movement flourished in Lithuania in the interwar period.